Ideological proximity, issue importance, and vote choice. (February 2022) - Flavin, Patrick; Law, Wilson
Abstract: This paper investigates what proportion of voters select their candidate based on policy proximity in a spatial voting framework and evaluates policy proximity's importance for vote choices. We develop a novel procedure to identify proximity voting and directly estimate the weights of policies from vote choices. Using the American National Election Studies (ANES) for 1996–2008 and nationally representative replication data from Leeper and Robison's (2020) survey experiments, we find that more than 80% of voters choose the most policy proximate candidate. Among these voters, we find that a one standard deviation change in relative proximity for an extremely important issue has a similar substantive effect on vote choice as partisan identification (moving from Independent to a Not Very Strong Democrat or Republican). Together, these findings suggest that policy positions and issue importance influence citizens' vote choices even after controlling for party identification and demographic characteristics.